Diversified Currency Holdings and Exchange Rate Dynamics - Chung-Fu Lai; Shan-Kai Tsai (International Journal of Economics and Financial Issues, 2015)
In this study, we incorporate diversified currency holdings into the New Open Economy Macroeconomics (NOEM) model to explore the issue of exchange rates dynamics. The findings show that exchange rate overshooting occurs when diversified currency holdings are included in a two-country dynamic optimizing NOEM model, and the extent of the overshoot depends on the level of diversified currency holdings. Regarding welfare analysis, an expansionary monetary policy of the home country increases domestic welfare. Also, we find that current account plays an important role in the effect of monetary policy on exchange rates, the increase in the domestic money supply stimulates domestic consumption expenditure through the effects of current account improvements, resulting in exchange rate appreciation.